Is Earnings Management Informational or Opportunistic? Evidence from ASEAN Countries - Dewi Kusuma Wardani; Indra Wijaya Kusuma (Gadjah Mada International Journal of Business, 2012)
This study explores the informational and opportunistic characteristics of earnings management in ASEAN countries. Earnings management has an impact on the profitability of the companies. A positive relation between earnings management and future profitability reveals that earnings management is informational. However, negative a relation between earnings management and future profitability indicates that earnings management is opportunistic. This study uses data from the OSIRIS database. Four hundred and eighty five (485) companies from the Philippines, Indonesia, Malaysia, Singapore, and Thailand are used as a sample. This study focuses on 2 types of earnings management: (1) accrual earnings management and (2) real earning management. Modified Jones model is used for the accrual earnings management. Real earnings management follows Roychowdury (2006). The results show that the characteristics of earnings management are not consistent. Real earnings management is informational in Thailand, but opportunistic in Indonesia. Accruals earnings management is informational in the Philippines, but opportunistic in Malaysia. Country factors such as culture may explain the inconsistency of the results in ASEAN.Keywords: accruals earnings management; ASEAN countries; future profitability; informational; opportunistic; real earnings management